2007
DOI: 10.1111/j.1365-4632.2007.03269.x
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir‐induced neuropsychosis successfully recovered after immediate hemodialysis in an end‐stage renal disease patient

Abstract: A 70-year-old man developed herpes zoster over the right L5-S2 region for 3 days and was admitted for acyclovir therapy. He had a medical history of rectal cancer status post-colostomy and end-stage renal disease undergoing thrice weekly hemodialysis. Without a prior loading dose, acyclovir 500 mg (7.7 mg/kg) daily was given intravenously in two divided doses. On the third dosage, the patient became confused and agitated and developed insomnia. Within the following 24 h, delirium, visual and auditory hallucina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…Haemodialysis of the agent was also reported. 11 In conclusion, the present report describes a case of delirium following brivudin treatment. To our knowledge, no such side effect of brivudin has been observed to date.…”
Section: Case Reportmentioning
confidence: 65%
See 2 more Smart Citations
“…Haemodialysis of the agent was also reported. 11 In conclusion, the present report describes a case of delirium following brivudin treatment. To our knowledge, no such side effect of brivudin has been observed to date.…”
Section: Case Reportmentioning
confidence: 65%
“…Some drugs have been reported to cause delirium, including the antimicrobials, clarithromycin and ciprofloxacin, 7,8 and antivirals, such as oseltamivir and acyclovir. [10][11][12] However, there is no record concerning the present case of delirium due to brivudin treatment was encountered. The patient was not taking any other medications that included delirium as a side effect, and did not have any other conditions that would explain his symptoms.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Acyclovir-induced neurotoxicity can present with a variety of symptoms including agitation, delirium and hallucinations. 21 Dose reductions are recommended in patients with renal impairment and in the elderly. Our patient received acyclovir at 800 mg/day for 24 months and a dose reduction was attempted, inflammation in the anterior chamber developed.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to zoster encephalitis, acyclovir neurotoxicity is associated with normal CSF findings and normal CT scan and MRI findings. Withdrawal of acyclovir often leads to resolution of neurological symptoms in 48–72 h,8 10 13 but some patients require haemodialysis 8 9 12 15. Some authors have suggested a therapeutic trial of haemodialysis to help distinguish the two conditions 8 9.…”
Section: Discussionmentioning
confidence: 99%